Intra-Articular Cellular Therapy for Osteoarthritis and Focal Cartilage Defects of the Knee: A Systematic Review of the Literature and Study Quality Analysis. (21st September 2016) - Chahla, Jorge; Piuzzi, Nicolas S.; Mitchell, Justin J.; Dean, Chase S.; Pascual-Garrido, Cecilia; LaPrade, Robert F.; Muschler, George F.
Abstract : Background: Intra-articular cellular therapy injections constitute an appealing strategy that may modify the intra-articular milieu or regenerate cartilage in the settings of osteoarthritis and focal cartilage defects. However, little consensus exists regarding the indications for cellular therapies, optimal cell sources, methods of preparation and delivery, or means by which outcomes should be reported. Methods: We present a systematic review of the current literature regarding the safety and efficacy of cellular therapy delivered by intra-articular injection in the knee that provided a Level of Evidence of III or higher. A total of 420 papers were screened. Methodological quality was assessed using a modified Coleman methodology score. Results: Only 6 studies (4 Level II and 2 Level III) met the criteria to be included in this review; 3 studies were on treatment of osteoarthritis and 3 were on treatment of focal cartilage defects. These included 4 randomized controlled studies without blinding, 1 prospective cohort study, and 1 retrospective therapeutic case-control study. The studies varied widely with respect to cell sources, cell characterization, adjuvant therapies, and assessment of outcomes. Outcome was reported in a total of 300 knees (124 in the osteoarthritis studies and 176 in the cartilage defect studies). Mean follow-up was 21.0 months (range, 12 to 36 months). All studies reported improved outcomes with intra-articular cellular therapy and no major adverse events. The mean modified Coleman methodology score was 59.1 ± 16 (range, 32 to 82). Conclusions: The studies of intra-articular cellular therapy injections for osteoarthritis and focal cartilage defects in the human knee suggested positive results with respect to clinical improvement and safety. However, the improvement was modest and a placebo effect cannot be disregarded. The overall quality of the literature was poor, and the methodological quality was fair, even among Level-II and III studies. Effective clinical assessment and optimization of injection therapies will demand greater attention to study methodology, including blinding; standardized quantitative methods for cell harvesting, processing, characterization, and delivery; and standardized reporting of clinical and structural outcomes. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.